Algebraic Curves and Finite Fields 2014
DOI: 10.1515/9783110317916.179
|View full text |Cite
|
Sign up to set email alerts
|

NTRU cryptosystem: Recent developments and emerging mathematical problems in finite polynomial rings

Abstract: The NTRU public-key cryptosystem, proposed in 1996 by Hoffstein, Pipher and Silverman, is a fast and practical alternative to classical schemes based on factorization or discrete logarithms. In contrast to the latter schemes, it offers quasi-optimal asymptotic efficiency and conjectured security against quantum computing attacks. The scheme is defined over finite polynomial rings, and its security analysis involves the study of natural statistical and computational problems defined over these rings. We survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Before we deal with the analysis of security infrastructure, it should be noted that the proposed method is based on algebraic infrastructure in the classic version of the NTRU. We can easily define the proposed authentication method based on its optimized versions .…”
Section: Analysis Of the Proposed Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Before we deal with the analysis of security infrastructure, it should be noted that the proposed method is based on algebraic infrastructure in the classic version of the NTRU. We can easily define the proposed authentication method based on its optimized versions .…”
Section: Analysis Of the Proposed Schemementioning
confidence: 99%
“…Moreover, given the NP‐hard nature of the SVP problem, this is impossible unless there occurs a rare event in mathematics and the complexity theory. The latest research regarding NTRU security shows that the cyclic structure in the NTRU lattice is not useful for the simplicity of the NTRU .…”
Section: Analysis Of the Proposed Schemementioning
confidence: 99%
“…It has been shown that fully homomorphic encryption (FHE) [21] schemes can be designed from NTRU [36], [41], [42]. The design, analysis and implementation of FHE is an active research area at the moment.…”
Section: Concl Usionmentioning
confidence: 99%
“…[9,10,14]) and is believed to remain secure in the presence of quantum computers. See the survey [23] for a complete description of the NTRU cryptosystem and its applications. In this paper, we consider the overstretched NTRU variant in the cyclotomic field K = Q[x]/(x n +1), with n a power of 2.…”
Section: Introductionmentioning
confidence: 99%